2016
DOI: 10.1002/btpr.2247
|View full text |Cite
|
Sign up to set email alerts
|

Effective recovery of poly‐β‐hydroxybutyrate (PHB) biopolymer from Cupriavidus necator using a novel and environmentally friendly solvent system

Abstract: This work demonstrates a significant advance in bioprocessing for a high-melting lipid polymer. A novel and environmental friendly solvent mixture, acetone/ethanol/propylene carbonate (A/E/P, 1:1:1 v/v/v) was identified for extracting poly-hydroxybutyrate (PHB), a high-value biopolymer, from Cupriavidus necator. A set of solubility curves of PHB in various solvents was established. PHB recovery of 85% and purity of 92% were obtained from defatted dry biomass (DDB) using A/E/P. This solvent mixture is compatibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 27 publications
3
26
0
Order By: Relevance
“…In the present study, the T m of polymer isolated using the alcoholic method was 179 °C and that obtained with the conventional method reached a T m of 176 °C. These values of T m are comparable with those reported by Fei et al and Fiorese et al for P(3HB) produced by Cupriavidus necator and recovered by extraction with propylene carbonate, acetone and ethanol at different temperatures (Table ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, the T m of polymer isolated using the alcoholic method was 179 °C and that obtained with the conventional method reached a T m of 176 °C. These values of T m are comparable with those reported by Fei et al and Fiorese et al for P(3HB) produced by Cupriavidus necator and recovered by extraction with propylene carbonate, acetone and ethanol at different temperatures (Table ).…”
Section: Resultssupporting
confidence: 91%
“…Several methods have been reported for the extraction of P(3HB) from the biomass of different organisms, and although these procedures are known to offer promising results, there are still obstacles for the efficient recovery of the biopolymer. Several studies in the literature have reported the use of nonhalogenated solvents . Most of these reports used polar or semi‐polar compounds, to solubilize nonpolar hydrophobic compounds, such as PHAs; therefore, in most of these studies it was necessary to use high temperatures (120–150 °C), as well as high pressures to improve the plastic extraction.…”
Section: Resultsmentioning
confidence: 99%
“…Reflux and Soxhlet extractions, with and without biomass pretreatments, have been described in literature for many different solvents [21][22][23][24]. Non-halogenated solvents have been the focus of many researches for their reduced toxicity, although the chlorinated ones, such as chloroform and dichloromethane, are still considered reference solvents because of their high efficiency [22,25,26]. The non-halogenated solvent dimethyl carbonate performs much better than a range of solvents such as diethyl carbonate, propylene carbonate and ethyl acetate and it achieved satisfactory yields of PHA recovery when compared to dichloromethane [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Fei et al, were also reported a novel solvent system for extracting PHB. They recovered PHB from C. necator dry biomass using acetone, ethanol and propylene carbonate (1:1:1).…”
Section: Resultsmentioning
confidence: 99%